Metagenomics and untargeted metabolomics reveal antibiotic resistance dynamics in an anaerobic digestion–composting system treating organic fraction of municipal solid waste - Elisabetta Fanfoni; Paolo Bellassi; Alessandra Fontana; Erika Sinisgalli; Gabriele Rocchetti; Sergio Piccinini; Lorenzo Morelli; Fabrizio Cappa (Environmental Microbiome)
Abstract Background The growing population and associated increase in municipal solid waste (MSW) have promoted the use of sustainable waste management strategies. Given its high organic content, MSW can be treated through anaerobic digestion (AD) and aerobic composting (AC) to recover value-added products such as bioenergy and soil amendments. However, MSW is also recognized as a relevant source of antibiotic resistance genes (ARGs), raising concerns about environmental and public health impacts. This study aimed to elucidate the dynamics of ARGs and antibiotic compounds during the treatment of the organic fraction of municipal solid waste (OFMSW) through an integrated AD–AC system. By combining metagenomics and untargeted metabolomics, a comprehensive characterization of shifts in the microbial community, ARGs, and antibiotic compounds throughout the treatment stages was achieved. Shotgun sequencing enabled an in-depth resistome analysis based on metagenome-assembled genomes (MAGs), while untargeted metabolomics revealed the occurrence and transformation of antibiotic compounds across the system. Results The integrated process resulted in a significant differentiation of microbial communities, resistome, and antibiotic compounds profiles, at different stages of the waste treatment plant. AD samples were mostly dominated by aminoglycoside and lincosamide ARGs, whereas AC samples by macrolide and rifamycin ARGs. Despite differences in drug class dominance, the composting process significantly increased both the ARGs diversity (i.e., digestate: H = 2.6 ± 0.1; mature compost: H = 3.7 ± 0.1) and abundance (i.e., mature compost vs. digestate: log2(FC) = 3.7). Untargeted metabolomics revealed distinct distributions of antibiotics among the six matrices (i.e., pulp, digestate, solid fraction, liquid fraction, fresh compost, and mature compost) suggesting limited degradation or transformation of some classes during treatment. Digestate was enriched in phenazines and trimethoprim derivatives, whereas mature compost mainly included phenicols and sulfonamides. Conclusions This study provides valuable insights into the fate of antibiotic resistance genes and the persistence of antibiotic compounds in an integrated AD and AC system treating OFMSW. Moreover, it was shown how the integration of -omics techniques as metagenomics and metabolomics can be systematically utilized to detect emerging ARGs and antibiotic compounds dynamics and monitor their ongoing evolution in biological waste treatment plants.